Molecular detection of in-vivo microbial contamination of metallic orthodontic brackets by checkerboard DNA-DNA hybridization - Damiao Andrucioli, Marcela Cristina; Nelson-Filho, Paulo; Nakane Matsumoto, Mirian Aiko; Pereira Saraiva, Maria Conceicao; Feres, Magda; de Figueiredo, Luciene Cristina; Martins, Lidia Parsekian [UNESP] (Mosby-elsevier, 2012)
Introduction: Knowing the microbiota that colonizes orthodontic appliances is important for planning strategies and implementing specific preventive measures during treatment. The purpose of this clinical trial was to evaluate in vivo the contamination of metallic orthodontic brackets with 40 DNA probes for different bacterial species by using the checkerboard DNA-DNA hybridization (CDDH) technique. Methods: Eighteen patients, 11 to 29 years of age having fixed orthodontic treatment, were enrolled in the study. Each subject had 2 new metallic brackets bonded to different premolars in a randomized manner. After 30 days, the brackets were removed and processed for analysis by CDDH. Data on bacterial contamination were analyzed descriptively and with the Kruskal-Wallis and Dunn post tests (alpha = 0.05). Forty microbial species (cariogenic microorganisms, bacteria of the purple, yellow, green, orange complexes, "red complex + Treponema socranskii," and the cluster of Actinomyces) were assessed. Results: Most bacterial species were present in all subjects, except for Streptococcus constellatus, Campylobacter rectus, Tannerella forsythia, T socranskii, and Lactobacillus acidophillus (94.4%), Propionibacterium acnes I and Eubacterium nodatum (88.9%), and Treponema denticola (77.8%). Among the cariogenic microorganisms, Streptococcus mutans and Streptococcus sobrinus were found in larger numbers than L acidophillus and Lactobacillus casei (P < 0.001). The periodontal pathogens of the orange complex were detected in larger numbers than those of the "red complex + T socranskii" (P < 0.0001). Among the bacteria not associated with specific pathologies, Veillonella parvula (purple complex) was the most frequently detected strain (P < 0.0001). The numbers of yellow and green complex bacteria and the cluster of Actinomyces were similar (P > 0.05). Conclusions: Metallic brackets in use for 1 month were multi-colonized by several bacterial species, including cariogenic microorganisms and periodontal pathogens, reinforcing the need for meticulous oral hygiene and additional preventive measures to maintain oral health in orthodontic patients. (Am J Orthod Dentofacial Orthop 2012;141:24-9)